Synthesis and utility of new amine/nucleobase addition products of allenylphosphonates - Swamy, K. C. Kumara; Balaraman, Ekambaram; Kumar, N. Satish (Tetrahedron, 2006)
In the reaction of allenylphosphonates with amines/nucleobases, depending on the amine and the allenylphosphonate, either Z- or E-vinylphosphonate or allylphosphonate as a single isomer with a β-amino functionality was isolated. A simple route to phosphonates with a β-NH2 group is developed by direct reaction with ammonia. In reactions with adenine, three different modes of reaction, with one of them involving an unusual cyclisation, are observed. The utility of (enamino)allyl phosphonate products thus obtained in the synthesis of (enamino)-1,3-butadienes via Horner–Wadsworth–Emmons (HWE) reaction is also demonstrated.

Unusual products in the reactions of phosphorus(III) compounds with N=N, C equivalent to C or conjugated double-bonded systems - Swamy, K. C. Kumara; Balaraman, Ekambaram; Pavan, M. Phani; Kumar, N. N. Bhuvan; Kumar, K. Praveen; Kumar, N. Satish (Journal of Chemical Sciences, 2006)
The diversity of products in the reaction of diethyl azodicarboxylate (DEAD)/diisopropyl azodicarboxylate (DIAD) and activated acetylenes with PIII compounds bearing oxygen or nitrogen substituents is discussed. New findings that are useful in understanding the nature of intermediates involved in the Mitsunobu reaction are highlighted. X-ray structures of two new compounds (2-t-Bu-4-MeC6H3O)P (μ-N-t-Bu)2P+[(NH-t-Bu)N[(CO2]-i-Pr)(HNCO2-i-Pr)]](Cl-)(2-t-Bu-4-MeC6H3OH)(23)and [CH2(6-t-Bu-4-Me-C6H2O)2P(O)C(CO2Me)C-(CO2Me)CClNC(O)Cl] (33) are also reported. The structure of23 is close to one of the intermediates proposed in the Mitsunobu reaction.

Convenient chromatography-free access to enantio-pure 6,6’-di-tert-butyl-1,1’- binaphthalene-2,2’-diol- its 3,3’-dibromo, di-tert-butyl and phosphorus derivatives: utility in asymmetric synthesis - Balaraman, Ekambaram; Swamy, K. C. Kumara (Tetrahedron-Asymmetry, 2007)
A simple chromatography-free high-yielding synthesis of the hexane-soluble enantiopure 6,6′-di-tert-butyl-1,1′-binaphthalene-2,2′-diol 3 (6,6′-di-tert-butyl BINOL) using Friedel–Crafts reaction on 1,1′-binaphthalene-2,2′-diol 1 (BINOL) is described. The enantiomeric purity was fully maintained in the reaction. Compound 3 has been used as an entry point for the convenient chromatography-free synthesis of 3,3′,6,6′-tetra-tert-butyl BINOL 4 and 3,3′-dibromo-6,6′-di-tert-butyl BINOL 5. A straightforward route to enantiopure bisphosphites [(6,6′-R2C20H10O2)P]2[O2C20H10-6,6′-R2] [R = H 15, t-Bu 16] by simply reacting phosphorochloridite (6,6′-R2C20H10O2)PCl [R = H 20, t-Bu 6] with metallic sodium is highlighted. The identity of 15 and 16 as their selenium-oxidized products 17 and 18 (at phosphorus center) is confirmed by X-ray crystallography (17 in the enantiopure form and 18 as racemate). Various enantiopure phosphoramidites of the modified BINOL have been synthesized. It is established that even when the phosphoramidites derived from the unsusbstituted BINOL 1 fail to give an appreciable optical induction in the asymmetric reduction of acetophenone/phenacyl chloride, those derived from 3 do induce moderate chiral induction (up to 30% ee in the case for acetophenone and 43% ee in the case of phenacyl chloride), thus leaving scope for further improvement in ee for related reactions.

Hydrophosphonylation of activated alkenes and alkynes via fluoride ion activation in ionic liquid medium - Balaraman, Ekambaram; Srinivas, Venu; Swamy, K. C. Kumara (Tetrahedron, 2009)
A simple transition metal-free hydro/hydrothiophosphonylation of Baylis–Hillman adducts, substituted allyl bromides, allenylphosphonates and alkynes, promoted by fluoride ion in ionic liquid, is described. Clear-cut evidence for fluoride activation of the phosphite via pentacoordinate phosphorus is provided for the first time. Also, in a comparative reaction, the product obtained was different from that from the palladium catalyzed one. Structures of key products are proven by X-ray crystallography.

Mitsunobu and related reactions: advances and applications - Swamy, K. C. Kumara; Kumar, N. N. Bhuvan; Balaraman, Ekambaram; Kumar, K. V. P. Pavan (Chemical Reviews, 2009)

Direct hydrogenation of amides to alcohols and amines under mild conditions - Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Shimon, Linda J. W.; Milstein, David (Journal of the American Chemical Society, 2010)
The selective, direct hydrogenation of amides to the corresponding alcohols and amines with cleavage of the C−N bond was discovered. The expected products of C−O cleavage are not formed (except as traces in the case of anilides). The reaction proceeds under mild pressure and neutral, homogeneous conditions using a dearomatized, bipyridyl-based PNN Ru(II) pincer complex as a catalyst. The postulated mechanism involves metal−ligand cooperation by aromatization−dearomatization of the heteroaromatic pincer core and does not involve hydrolytic cleavage of the amide. The simplicity, generality, and efficiency of this environmentally benign process make it attractive for the direct transformations of amides to alcohols and amines in good to excellent yields.

Alkynyl and phosphonyl substituted nucleobases: a case of thermally induced conformational polymorphism - Swamy, K. C. Kumara; Allu, Srinivasarao; Srinivas, Venu; Balaraman, Ekambaram; Kumar, K. V. P. Pavan (Crystal Growth & Design, 2011)
Substituted nucleobases with alkynyl and phosphonyl groups were investigated in the context of supramolecular interactions and possible use toward synthesis of nucleoside phosphonic acids (NPAs). The adeninyl compound (adeninyl-N-9)-CH2CH2CH2CH2C≡CH exhibits conformational polymorphism as revealed by X-ray structures determined at 200 and 298 K. Interestingly, in the compound (adeninyl-N-9)-(CH2)15CH3, the long aliphatic carbon chain does not show disorder. A rather unusual bending of alkyl chain, likely due to C–H···O interactions, is observed in the case of the thymine compound (thyminyl)-CH2CH2CH2C≡CH that possesses a terminal alkyne group. The powerful hydrogen bond acceptor property of the phosphoryl oxygen (P═O) does not perturb (unless assisted by other hydrogen bonding partners) the homo base-pairing in the structures of most of the phosphonyl substituted nucleobases studied.

Cyclodiphosph(III)azane chemistry – ylides from the reaction of [(RNH)P-N(t-Bu)]2 [R = t-Bu, i-Pr] with dimethyl maleate and chiral ansa-type derivatives from reaction of [ClP-N(t-Bu)]2 with a substituted BINOL - Swamy, K.C. Kumara; Gangadhararao, G.; Srinivas, Venu; Kumar, N. N. Bhuvan; Balaraman, Ekambaram; Chakravarty, Manab (Inorganica Chimica Acta, 2011)
Use of a simple inorganic ring system with the cyclodiphosph(III)azane skeleton [e.g. [(RNH)P-N(t-Bu)]2 [R = t-Bu (7), i-Pr (8)] to probe some of the intermediates proposed in phosphine mediated organic reactions is highlighted. Thus the reaction of 7–8 with the allenylphosphine oxide Ph2P(O)C(Ph)double bond; length as m-dashCdouble bond; length as m-dashCH2 (9) affords the phosphinimines [(RNH)P(μ-N-t-Bu)2P(double bond; length as m-dashN-R)-C(double bond; length as m-dashCH2)CH(Ph)-P(O)Ph2] [R = t-Bu (10), i-Pr (11)], while a similar reaction of 7–8 with dimethyl maleate (or dimethyl fumarate) affords the ylides [(RNH)P(μ-N-t-Bu)2P(NH-R)double bond; length as m-dashC(CO2Me)-CH2(CO2Me) [R = t-Bu (18), i-Pr (19)]. The implication of such reactions on phosphine mediated organic transformations including Morita–Baylis–Hillman reaction is mentioned. In a rather rare type of situation, an unusually long phosphoryl (Pdouble bond; length as m-dashO) bond [1.538 (5) Å] as revealed the X-ray structure of {(R)-6,6′-(t-Bu)2-1,1′-(C10H5)2-2,2′-O2-}{P(O)(N-t-Bu)2-P(Se)} (27) is rationalized by means of crystallographic disorder in packing after comparing the data with that in the literature and {1,1′-(C10H6)2-2,2′-O2}{P(Se)(N-t-Bu)2-P(Se)} (29). X-ray structures of the new compounds 10–11, 18–19, 27 and 29 are discussed. Compound 10 crystallizes in the chiral space group Pca2(1) with (S)-chirality at the carbon center [–C(double bond; length as m-dashCH2)CH(Ph)-P] suggesting a case of spontaneous resolution through crystallization.

Efficient hydrogenation of organic carbonates, carbamates, and formates indicates alternative routes to methanol based on CO2 and CO - Balaraman, Ekambaram; Gunanathan, Chidambaram; Zhang, Jing; Shimon, Linda J. W.; Milstein, David (Nature Chemistry, 2011)
Catalytic hydrogenation of organic carbonates, carbamates and formates is of significant interest both conceptually and practically, because these compounds can be produced from CO2 and CO, and their mild hydrogenation can provide alternative, mild approaches to the indirect hydrogenation of CO2 and CO to methanol, an important fuel and synthetic building block. Here, we report for the first time catalytic hydrogenation of organic carbonates to alcohols, and carbamates to alcohols and amines. Unprecedented homogeneously catalysed hydrogenation of organic formates to methanol has also been accomplished. The reactions are efficiently catalysed by dearomatized PNN Ru(II) pincer complexes derived from pyridine- and bipyridine-based tridentate ligands. These atom-economical reactions proceed under neutral, homogeneous conditions, at mild temperatures and under mild hydrogen pressures, and can operate in the absence of solvent with no generation of waste, representing the ultimate ‘green’ reactions. A possible mechanism involves metal–ligand cooperation by aromatization–dearomatization of the heteroaromatic pincer core.

Electron-rich PNP- and PNN-type Ru(II) hydrido-borohydride complexes. synthesis, structure and catalytic activity towards dehydrogenation of alcohols and hydrogenation of esters - Zhang, Jing; Balaraman, Ekambaram; Leitus, Gregory; Milstein, David (Organometallics, 2011)
Electron-rich PNP- and PNN-type ruthenium(II) hydrido borohydride pincer complexes, [RuH(BH4)(tBu-PNP)] (tBu-PNP = (2,6-bis(di-tert-butylphosphinomethyl)pyridine) (5) and [RuH(BH4)(tBu-PNN)] (tBu-PNN = 2-di-tert-butylphosphinomethyl-6-diethylaminomethylpyridine) (6), were prepared from their corresponding N2-bridged dinuclear Ru(II) complexes [(tBu-PNP)RuCl2]2(μ-N2) (3) and [(tBu-PNN)RuCl2]2(μ-N2) (4), respectively. The X-ray structure of 5 reveals a BH4– anion η2 coordinated to ruthenium through two bridging hydrides. A variable-temperature 1H NMR study of 6 exhibits interesting fluxional behavior of the BH4– ligand. Similarly, the Ru(II) hydrido borohydride complex 9, in which the BH4– moiety is coordinated in a η1 bonding mode, was obtained by reaction of [RuCl2(PPh3)(iPr-PNP)] (iPr-PNP = 2,6-bis(diisopropylphosphinomethyl)pyridine) (8) with two equivalents of NaBH4 at room temperature. The hydrido borohydride pincer complexes 5, 6, and 9 catalyze the acceptorless dehydrogenative coupling of primary alcohols to esters and the dehydrogenation of secondary alcohols to the corresponding ketones, accompanied by evolution of hydrogen gas. The reactivity follows the order 6 > 9 > 5. With the hydrido borohydride complex 6 as catalyst, high yields (up to 98%) and high turnover numbers (TON ∼1000) were obtained in the dehydrogenation of primary alcohols under mild and neutral conditions. In addition, 6 effectively catalyzes the hydrogenation of nonactivated aromatic and aliphatic esters to the corresponding alcohols with TON ∼200 under a relatively mild pressure of dihydrogen and neutral and homogeneous conditions. Thus, an efficient homogeneous catalytic system for the dehydrogenation–hydrogenation reactions of alcohols is developed, which is relevant to the current interest in hydrogen storage.

New CNN-type ruthenium pincer NHC complexes. synthesis and catalytic activity. mild, efficient hydrogenation of esters - Fogler, Eran; Balaraman, Ekambaram; Ben-David, Yehoshoa; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2011)
New pincer ruthenium complexes (2–6) based on the new bipyridine-NHC ligand 1 were prepared and studied, resulting in an efficient catalytic hydrogenation of esters to the corresponding alcohols under mild conditions. Reaction of the ligand 1 with RuH(Cl)CO(PPh3)3, followed by reaction with one equivalent of the base KHMDS, gave the mixed phosphine-NHC complex 2, incorporating a C–H-activated bipyridine ligand. Complex 2 has an octahedral structure containing two phosphorus atoms trans to each other, a hydride trans to the NHC ligand, and CO trans to the C–H-activated carbon of the bipyridine ligand. Using the precursor complex Ru(p-cymene)Cl2(CO), reaction with 1 followed by treatment of the intermediate product with one equivalent of KHMDS resulted in formation of the dichloride pincer complexes 3a and 3b, which are in equilibrium, as indicated by variable-temperature 1H NMR. Complex 3a is an octahedral, neutral, and symmetric complex with the CO ligand positioned trans to the central pyridine group of the pincer ligand and the two chlorides trans to each other, as indicated by single-crystal X-ray diffraction. Complex 3b is cationic, with an outer-sphere chloride. Reaction of the NHC ligand 1 with LiHMDS at low temperature followed by addition of RuH(Cl)CO(PPh3)3 resulted in the mixed phosphine-NHC complex 4, which has an octahedral structure containing phosphorus trans to the hydride, a CO trans to the NHC ligand, and an outer-sphere chloride. Chloride substitution by BArF– gave the X-ray-characterized complex 5. Deprotonation of complex 4 with KHMDS resulted in formation of the dearomatized complex 6. The in situ prepared 6 (from complex 4 and an equivalent of base) is among the best catalysts known for the hydrogenation of nonactivated esters to the corresponding alcohols under mild conditions.

Photocatalytic splitting of CS2 to a carbon-sulfur polymer and S8 catalyzed by a bimetallic ruthenium(II) compound with a tertiary amine binding site - towards photocatalytic splitting of CO2? - Livanov, Konstantin; Madhu, Vedichi; Balaraman, Ekambaram; Shimon, Linda J. W.; Diskin-Posner, Yael; Neumann, Ronny (Inorganic Chemistry, 2011)
The catalytic photocleavage of CS2 to S8 and a (CxSy)n polymer with visible light using a dinuclear ruthenium(II) compound with a bipyridine units for photoactivity and a vicinal tertiary amine binding site for CS2 activation was studied. The catalyst was characterized by X-ray diffraction, 1H NMR, and 13C NMR, ESI-MS and elemental analysis. CS2 photocleavage was significant (240 turnovers, 20 h) to yield isolable S8 and a (CxSy)n polymer. A mononuclear catalyst or one without an amine binding site showed significantly less activity. XPS of the (CxSy)n polymer showed a carbon/sulfur ratio ∼1.5–1.6 indicating that in part both C–S bonds of CS2 had been cleaved. Catalyst was also included within the polymer. The absence of peaks in the 1H NMR verified the (CxSy)n nature of the polymer, while 13C NMR and IR indicated that the polymer had multiple types of C–S and C–C bonds.

Synthesis of peptides and pyrazines from beta-aminoalcohols via extrusion of H2 catalyzed by ruthenium pincer complexes. ligand controlled selectivity - Gnanaprakasam, Boopathy; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Angewandte Chemie, 2011)
Bitte wählen: Die Wahl des Katalysators, eines Ru-Pinzettenkomplexes, bestimmt, ob Peptide oder Pyrazine aus β-Aminoalkoholen entstehen: Der PNN-Komplex 1 führt, je nach Substituent R (siehe Schema), zu linearem Polyalanin oder zu cyclischen Dipeptiden, der PNP-Komplex 2 katalysiert die Bildung von Pyrazinen. Die Reaktionen finden in homogener Lösung unter neutralen Bedingungen statt.

Unprecedented catalytic hydrogenation of urea derivatives to amines and methanol - Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Angewandte Chemie, 2011)
Indirekte CO2-Hydrierung: Eine Hydrierung von Harnstoffen zu Aminen und Methanol (siehe Bild) wird durch einen RuII-Pinzettenkomplex mit dreizähnigem bipyridinbasiertem PNN-Liganden katalysiert und verläuft unter milden, neutralen Bedingungen bei einem H2-Druck von 13.6 atm. Da sich Harnstoffderivate ausgehend von CO2 erhalten lassen, ermöglicht dieser Ansatz die indirekte Hydrierung von Kohlendioxid zu Methanol.

Efficient hydrogenation of biomass derived cyclic di-esters to 1,2-diols - Balaraman, Ekambaram; Fogler, Eran; Milstein, David (Chemical Communications, 2012)
The unprecedented homogeneous hydrogenation of cyclic di-esters, in particular biomass-derived glycolide and lactide, to the corresponding 1,2-diols is catalyzed by Ru(II) PNN (1) and Ru(II) CNN (2) pincer complexes under mild hydrogen pressure and (in the case of 1) neutral conditions. No racemization was observed when a chiral di-ester was used.

Novel ruthenium complexes and their uses in processes for formation and/or hydrogenation of esters, amides and derivatives thereof - Milstein, David; Balaraman, Ekambaram; Gunanathan, Chidambaram; Gnanaprakasam, Boopathy; Zhang, Jing (EP2629889A2, US9045381, US20130281664, WO2012052996A2, WO2012052996A3, 2012)
The present invention relates to novel Ruthenium complexes and related borohydride complexes, and their use for (1) hydrogenation of amides (including polyamides) to alcohols and amines; (2) preparing amides from alcohols with amines (including preparing polyamides (e.g., polypeptides) by reacting dialcohols and diamines or by polymerization of amino alcohols); (3) hydrogenation of esters to alcohols (including hydrogenation of cyclic esters (lactones), cyclic di-esters (di-lactones) or polyesters); (4) hydrogenation of organic carbonates (including polycarbonates) to alcohols and of carbamates (including polycarbamates) or urea derivatives to alcohols and amines; (5) dehydrogenative coupling of alcohols to esters; (6) hydrogenation of secondary alcohols to ketones; (7) amidation of esters (synthesis of amides from esters and amines); (8) acylation of alcohols using esters; (9) coupling of alcohols with water to form carboxylic acids; and (10) dehydrogenation of beta-amino alcohols to form pyrazines. The present invention further relates to novel uses of certain pyridine Ruthenium complexes.

Ruthenium pincer-catalyzed cross-dehydrogenative coupling of primary alcohols with secondary alcohols under neutral conditions - Srimani, Dipankar; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2012)
Cross-dehydrogenative coupling of primary alcohols with secondary alcohols to obtain mixed esters with the liberation of molecular hydrogen is achieved in high yield and good selectivity under neutral conditions, using a bipyridyl-based PNN ruthenium(II) pincer catalyst.

Synthesis of polyamides from diols and diamines with liberation of H2 - Gnanaprakasam, Boopathy; Balaraman, Ekambaram; Gunanathan, Chidambaram; Milstein, David (Journal of Polymer Science Part A: Polymer Chemistry, 2012)
The amidation reaction based on catalytic coupling of alcohols with amines previously reported by us, using the pincer complexes 1 and 2 as catalysts, was applied to the generation of polyamides from nonactivated diols and diamines. A range of polymers was prepared, with Mn up to 26.9 kDa. Unlike the traditional syntheses of polyamides based on carboxylic acid derivatives, which require the use of toxic reagents and generate stoichiometric amounts of waste, this process generates only molecular hydrogen as byproduct. Both aromatic and aliphatic diols and diamines were used. Gel permeation chromatography measurements of the dimethylformamide-soluble polymers and thermal studies of the polyamides were performed. Matrix assisted laser desorption/ionization time-of-flight (MALDI-TOF) spectra are also reported. Thermogravimetric analyses studies indicate that the aromatic polyamides (with the exception of the pyridine-based polyamide) are more thermally stable than the aliphatic ones. This general, environmentally benign method for the synthesis of polyamides is homogeneously catalyzed under neutral conditions by dearomatized ruthenium-pincer complexes 1 and 2 and proceeds in 1,4-dioxane under an inert atmosphere. Conditions for polyamidation in the absence of solvent are also reported, using the pincer complex 2 as catalyst. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2012

Use of ruthenium complexes for formation and/or hydrogenation of amides and related carboxylic acid derivatives - Milstein, David; Gunanathan, Chidambaram; Ben-David, Yehoshoa; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Zhang, Jing (US20120253042, US20160152663, 2012)
A process for preparing amides by reacting a primary amine and a primary alcohol in the presence of a Ruthenium complex to generate the amide and molecular hydrogen. Primary amines are directly acylated by equimolar amounts of alcohols to produce amides and molecular hydrogen (the only byproduct) in high yields and high turnover numbers. Also disclosed are processes for hydrogenation of amides to alcohols and amines; hydrogenation of organic carbonates to alcohols; hydrogenation of carbamates or urea derivatives to alcohols and amines; amidation of esters; acylation of alcohols using esters; coupling of alcohols with water and a base to form carboxylic acids; dehydrogenation of beta-amino alcohols to form pyrazines and cyclic dipeptides; and dehydrogenation of secondary alcohols to ketones. These reactions are catalyzed by a Ruthenium complex which is based on a dearomatized PNN-type ligand of formula A1 or precursors thereof of formulae A2 or A3.

Catalytic transformation of alcohols to carboxylic acid salts and H2 using water as the oxygen atom source - Balaraman, Ekambaram; Khaskin, Eugene; Leitus, Gregory; Milstein, David (Nature Chemistry, 2013)
The oxidation of alcohols to carboxylic acids is an important industrial reaction used in the synthesis of bulk and fine chemicals. Most current processes are performed by making use of either stoichiometric amounts of toxic oxidizing agents or the use of pressurized dioxygen. Here, we describe an alternative dehydrogenative pathway effected by water and base with the concomitant generation of hydrogen gas. A homogeneous ruthenium complex catalyses the transformation of primary alcohols to carboxylic acid salts at low catalyst loadings (0.2 mol%) in basic aqueous solution. A consequence of this finding could be a safer and cleaner process for the synthesis of carboxylic acids and their derivatives at both laboratory and industrial scales.

Formation of tertiary amides and H2 by dehydrogenative coupling of primary alcohols with secondary amines catalyzed by ruthenium bipyridine-based pincer complexes - Srimani, Dipankar; Balaraman, Ekambaram; Hu, Peng; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2013)
Dehydrogenative coupling of primary alcohols with secondary amines to form tertiary amides and dihydrogen (H2) is efficiently catalyzed by bipyridyl-based ruthenium pincer complexes (0.2–1 mol%) under neutral conditions (in case of the dearomatized complexes), or with added catalytic amount of base. The reaction is sensitive to steric hindrance; in the case of amidation of bulky secondary amines a less sterically hindered complex is more efficient. Selective acylation of primary amines in the presence of secondary amines was also demonstrated.

PNN-Ru pincer complexes based on phosphinated 2,2’-dipyridinemethane- and 2,2’-oxobispyridine. metal-ligand cooperation in cyclometallation and catalysis - Barrios-Francisco, Rigoberto; Balaraman, Ekambaram; Diskin-Posner, Yael; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2013)
The synthesis of novel PNN ruthenium pincer complexes based on 2,2′-dipyridinemethane phosphine derivatives, as well as on 2,2′-oxobispyridine phosphine ligands, and their reactivity toward dearomatization and cyclometalation are described. The dearomatized compounds 7a,b undergo cyclometalation to yield complexes 8a,b. In order for cyclometalation to proceed, the coordination sphere around the Ru center has to rearrange, and this depends on the flexibility of the system, showing that the cyclometalation is qualitatively faster in the case of the dimethyl derivative 7a than in the case of the spyrocyclopentyl derivative 7b. The cyclometalation occurs diastereoselectively and leads to only one diastereomer of the cyclometalated compounds. In the case of the 2,2′-oxobispyridine complex 6c, the dearomatized complex was too unstable to be isolated; however it was possible to isolate and characterize a stable dicarbonyl-dearomatized ruthenium(II) complex, 9c, when the deprotonation was performed under a CO atmosphere. Dearomatization of 6a under CO also led to dicarbonyl-dearomatized ruthenium(II) complex 9a, which slowly rearranged into the dicarbonyl-aromatized ruthenium(0) complex 10a. These complexes were tested in catalytic alcohol–amine coupling, esterification of primary alcohols, and hydrogenation of secondary amides. Moderate activity was observed in hydrogenation of amides to alcohols and amines and low activity in the other transformations, owing mainly to the formation of stable cyclometalated compounds.

Stepwise metal-ligand cooperation via a reversible aromatization-deconjugation-sequence in ruthenium complexes with a tetradentate phenanthroline-based ligand - Langer, Robert; Fuchs, Ido; Vogt, Matthias; Balaraman, Ekambaram; Diskin-Posner, Yael; Shimon, Linda J. W.; Ben-David, Yehoshoa; Milstein, David (Chemistry - A European Journal, 2013)
The synthesis and reactivity of ruthenium complexes containing the tetradentate phenanthroline-based phosphine ligand 2,9-bis((di-tert-butylphosphino)methyl)-1,10-phenanthroline (PPhenP) is described. The hydrido chloro complex [RuHCl(PPhenP)] (2) undergoes facile dearomatization upon deprotonation of the benzylic position, to give [RuH(PPhenP-H)] (4). Addition of dihydrogen to 4 causes rearomatization of the phenanthroline moiety to trans-[Ru(H)2(PPhenP)] (5), followed by hydrogenation of an aromatic heterocycle in the ligand backbone, to give a new dearomatized and deconjugated complex [RuH(PPhenP*-H)] (6). These aromatization/deconjugation steps of the coordinated ligand were demonstrated to be reversible and operative in the dehydrogenation of primary alcohols without the need for a hydrogen acceptor. This aromatization/deconjugation sequence constitutes an unprecedented mode of a stepwise cooperation between the metal center and the coordinated ligand.

Synthesis, structures, and dearomatization by deprotonation of iron complexes featuring bipyridine-based PNN pincer ligands - Zell, Thomas; Langer, Robert; Iron, Mark A.; Konstantinovski, Leonid; Shimon, Linda J. W.; Diskin-Posner, Yael; Leitus, Gregory; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Inorganic Chemistry, 2013)
The synthesis and characterization of new iron pincer complexes bearing bipyridine-based PNN ligands is reported. Three phosphine-substituted pincer ligands, namely, the known tBu-PNN (6-((di-tert-butylphosphino)methyl)-2,2′-bipyridine) and the two new iPr-PNN (6-((di-iso-propylphosphino)methyl)-2,2′-bipyridine) and Ph-PNN (6-((diphenylphosphino)methyl)-2,2′-bipyridine) ligands were synthesized and studied in ligation reactions with iron(II) chloride and bromide. These reactions lead to the formation of two types of complexes: mono-chelated neutral complexes of the type [(R-PNN)Fe(X)2] and bis-chelated dicationic complexes of the type [(R-PNN)2Fe]2+. The complexes [(R-PNN)Fe(X)2] (1: R = tBu, X = Cl, 2: R = tBu, X = Br, 3: R = iPr, X = Cl, and 4: R = iPr, X = Br) are readily prepared from reactions of FeX2 with the free R-PNN ligand in a 1:1 ratio. Magnetic susceptibility measurements show that these complexes have a high-spin ground state (S = 2) at room temperature. Employing a 2-fold or higher excess of iPr-PNN, diamagnetic hexacoordinated dicationic complexes of the type [(iPr-PNN)2Fe](X)2 (5: X = Cl, and 6: X = Br) are formed. The reactions of Ph-PNN with FeX2 in a 1:1 ratio lead to similar complexes of the type [(Ph-PNN)2Fe](FeX4) (7: X = Cl, and 8: X = Br). Single crystal X-ray studies of 1, 2, 4, 6, and 8 do not indicate electron transfer from the FeII centers to the neutral bipyridine unit based on the determined bond lengths. Density functional theory (DFT) calculations were performed to compare the relative energies of the mono- and bis-chelated complexes. The doubly deprotonated complexes [(R-PNN*)2Fe] (9: R = iPr, and 10: R = Ph) were synthesized by reactions of the dicationic complexes 6 and 8 with KOtBu. The dearomatized nature of the central pyridine of the pincer ligand was established by X-ray diffraction analysis of single crystals of 10. Reactivity studies show that 9 and 10 have a slightly different behavior in protonation reactions.

Hydrogenation of polar bonds catalysed by ruthenium-pincer complexes - Balaraman, Ekambaram; Milstein, David (Ruthenium in Catalysis, 2014)
Catalytic hydrogenation of polar bonds using molecular hydrogen is an important, atom-economical synthetic reaction. Classical reduction methods of polar bond often require reactive metal-hydride reagents in stoichiometric amount and produce copious waste. Hydrogenation of carbonyl compounds in particular provides `green' approaches to synthetically important building blocks, such as alcohols and amines. We have designed and synthesized several ruthenium-based pincer catalysts for unprecedented hydrogenation reactions including: (1) amides to alcohols and amines, (2) biomass-derived di-esters to 1,2-diols and (3) CO2 and CO derivatives to methanol. These atom-economical reactions operate under neutral, homogeneous conditions, at mild temperatures, mild hydrogen pressures, and can operate in absence of solvent with no generation of waste. The postulated mechanisms involve metal-ligand cooperation (MLC) by aromatization-dearomatization of the heteroaromatic pincer core.
Keywords: Amides; Carbon dioxide; Esters; Hydrogen; Hydrogenation; Metal-ligand cooperation; Pincer complexes; ruthenium

Direct synthesis of secondary amines from alcohols and ammonia catalyzed by a ruthenium pincer complex - Balaraman, Ekambaram; Srimani, Dipankar; Diskin-Posner, Yael; Milstein, David (Catalysis Letters, 2015)
Efficient and selective direct synthesis of secondary amines from primary alcohols and ammonia with liberation of water has been achieved, with high turnover numbers and with no generation of waste. In case of benzylic alcohols, imines rather than amines are obtained. This atom economical, environmentally benign reaction is homogenously catalyzed by a well-defined bipyridine based Ru(II)-PNN pincer complex.
Keywords: Alcohol; Ammonia; Homogenous catalysis; Ru-pincer complex; Secondary amine

Reversed reactivity of anilines with alkynes in the rhodium-catalysed C-H activation/carbonylation tandem - Midya, Siba Prasad; Sahoo, Manoj Kumar; Landge, Vinod Gokulkrishna; Rajamohanan, P. R.; Balaraman, Ekambaram (Nature Communications, 2015)
Development of multicatalytic approach consisting of two or more mechanistically distinct catalytic steps using a single-site catalyst for rapid and straightforward access of structurally complex molecules under eco-benign conditions has significance in contemporary science. We have developed herein a rhodium-catalysed C-H activation strategy which uses an unprotected anilines and an electron-deficient alkynes to C-C bonded products as a potential intermediate in contrast to the archetypical C-N bonded products with high levels of regioselectivity. This is followed by carbonylation of C-H bond activated intermediate and subsequent annulation into quinolines has been described. This rhodium-catalysed auto-tandem reaction operates under mild, environmentally benign conditions using water as the solvent and CO surrogates as the carbonyl source with the concomitant generation of hydrogen gas. The strategy may facilitate the development of new synthetic protocols for the efficient and sustainable production of chemicals in an atom-economic way from simple, abundant starting materials.

Reverse-hydroformylation: a missing reaction explored - Nandakumar, Avanashiappan; Sahoo, Manoj Kumar; Balaraman, Ekambaram (Organic Chemistry Frontiers, 2015)
Recent progress in transition-metal catalysed acceptor- and acceptorless-reverse hydroformylation of aldehydes for the conversion of olefins has been discussed. The aldehyde feedstock serves as a source for production of syngas and valuable alkenes.

Transition-metal-catalyzed hydrogen-transfer annulations: access to heterocyclic scaffolds - Nandakumar, Avanashiappan; Midya, Siba Prasad; Landge, Vinod Gokulkrishna; Balaraman, Ekambaram (Angewandte Chemie-International Edition, 2015)
The ability of hydrogen-transfer transition-metal catalysts, which enable increasingly rapid access to important structural scaffolds from simple starting materials, has led to a plethora of research efforts on the construction of heterocyclic scaffolds. Transition-metal-catalyzed hydrogen-transfer annulations are environmentally benign and highly atom-economical as they release of water and hydrogen as by-product and utilize renewable feedstock alcohols as starting materials. Recent advances in this field with respect to the annulations of alcohols with various nucleophilic partners, thus leading to the formation of heterocyclic scaffolds, are highlighted herein.

Well-defined palladium(II) complexes for ligand enabled C(sp3)-alkynylation - Landge, Vinod Gokulkrishna; Sahoo, Manoj Kumar; Midya, Siba Prasad; Jaiswal, Garima; Balaraman, Ekambaram (Dalton Transactions, 2015)
The first example of ligand-enabled C(sp3)-alkynylation of 8-methylquinoline is reported. The reaction is catalysed by well-defined Pd(II) complexes. The present C(sp3)-alkynylation has a broad substrate scope as well as functional group tolerance and proceeds efficiently under mild conditions.

Cobalt-catalyzed bis-alkynylation of amides via double C–H bond activation - Landge, Vinod Gokulkrishna; Jaiswal, Garima; Balaraman, Ekambaram (Organic Letters, 2016)
The first example of cobalt-catalyzed selective bis-alkynylation of amides via double C–H bond activation with the directing assistance of a removable bidentate auxiliary is reported. The developed alkynylation strategy is simple, efficient, and tolerant of various functional groups including ether, amine, halides, and heterocyclic motifs. The reaction can be scaled up under mild conditions.

Expedient cobalt-catalyzed C–H alkynylation of (enantiopure) benzylamines - Landge, Vinod Gokulkrishna; Midya, Siba Prasad; Rana, Jagannath; Shinde, Dinesh R.; Balaraman, Ekambaram (Organic Letters, 2016)
A unified strategy for cobalt-catalyzed ortho-C-H bond alkynylation of benzylamines is reported. Simple, commercially available CoBr2 was used as a cobalt source. The developed alkynylation strategy is robust and efficient and has a broad substrate scope including 1 degrees, 2 degrees, and 3 degrees benzylamines. The mechanistic study shows that C-H bond cleavage is reversible, and the kinetic study illustrates that the rate of reaction depends solely on the catalyst.
Keywords: Terminal Alkynes; Bond Activation; Directed Functionalization; Aminoquinoline Benzamides; Ortho-C(Sp(2))-H Bonds; Mechanistic Insights; Selective Access; Carbon-Hydrogen; Nickel; Annulation

Nickel-catalyzed direct alkynylation of C(sp2)-H bonds of amides: an “inverse sonogashira strategy” to ortho-alkynylbenzoic acids. just accepted - Landge, Vinod Gokulkrishna; Shewale, Chinmay H.; Jaiswal, Garima; Sahoo, Manoj Kumar; Midya, Siba Prasad; Balaraman, Ekambaram (Catalysis Science & Technology, 2016)
Nickel-catalyzed direct alkynylation of C(sp2)–H bonds of amides using commercially available, inexpensive 8-aminoquinoline as a removable bidentate directing group is described. The present ortho-alkynylation has a broad substrate scope, functional group tolerance and high regiocontrol, and can be scaled up. The efficiency and selectivity of this strategy provide sustainable routes to a diverse array of ortho-alkynylbenzoic acids under Ni(II)-catalyzed conditions.

Sustainable Iron-catalyzed direct imine formation by acceptorless dehydrogenative coupling of alcohols with amines - Jaiswal, Garima; Landge, Vinod Gokulkrishna; Jagadeesan, Dinesh; Balaraman, Ekambaram (Green Chemistry, 2016)
The Acceptorless Dehydrogenative Coupling (ADC) of alcohols with amines is reported using a heterogeneous Fe-catalyst. The reaction operates under mild conditions with the liberation of dihydrogen and water as the byproducts. The developed ADC strategy is simple, efficient, exhibits wide functional group tolerance and can be scaled up. The present catalytic approach possesses a dual role; acting as a catalyst as well as being magnetically separable. The sustainable reuse of a heterogeneous iron catalyst is also shown.

Iron-based nanocatalyst for the acceptorless dehydrogenation reactions - Jaiswal, Garima; Landge, Vinod G.; Jagadeesan, Dinesh; Balaraman, Ekambaram (Nature Communications, 2017)
Development of sustainable catalytic systems for fundamentally important synthetic transformations and energy storage applications is an intellectually stimulating challenge. Catalytic dehydrogenation of feedstock chemicals, such as alcohols and amines to value-added products with the concomitant generation of dihydrogen is of much interest in the context of hydrogen economy and is an effective alternative to the classical oxidation reactions. Despite a number of homogeneous catalysts being identified for the acceptorless dehydrogenation, the use of high price and limited availability of precious metals and poor recovery of the catalyst have spurred interest in catalysis with more earth-abundant alternatives, especially iron. However, no report has described a reusable iron-based heterogeneous catalyst for oxidant-free and acceptorless dehydrogenation reactions. Here we replace expensive noble metal catalysts with an inexpensive, benign, and sustainable nanoscale iron catalyst for the efficient acceptorless dehydrogenation of N-heterocycles and alcohols with liberation of hydrogen gas.

Iron-catalyzed dehydrogenation reactions and their applications in sustainable energy and catalysis - Balaraman, Ekambaram; Nandakumar, Avanashiappan; Jaiswal, Garima; Sahoo, Manoj K. (Catalysis Science & Technology, 2017)
Inspired by nature, chemists have designed new catalysts in the pursuit of selective bond activation and chemical transformations. Emergent biological systems often use earth-abundant first-row transition elements as catalytically active sites to facilitate specific and highly selective chemical processes. The design of a new catalytic system based on abundant and inexpensive catalysts, particularly the iron-based catalysts, for fundamentally significant synthetic transformations under environmentally benign conditions is an important paradigm in chemical synthesis. In recent times, iron-based catalytic systems have shown unprecedented reactivity in the acceptorless dehydrogenation reactions of feedstock chemicals, with the liberation of molecular hydrogen as the by-product, and have enabled greener chemical synthetic methods and alternative energy storage systems. Indeed, it has been demonstrated that the proper design of iron catalysts by judiciously choosing ligands, can aid in the development of new sustainable energy storage systems and catalysis. This tutorial review focuses on the recent development of iron-based dehydrogenation reactions of fundamentally important feedstock, as a route to sustainable chemical synthesis and energy storage applications. The emerging area of the iron-based dehydrogenation strategy provides an opportunity to make industrially applicable, cost-effective and environmentally benign catalytic systems.

Metal-free radical trifluoromethylation of beta-nitroalkenes through visible-light photoredox catalysis - Midya, Siba P.; Rana, Jagannath; Abraham, Thomas; Aswin, Bhaskaran; Balaraman, Ekambaram (Chemical Communications, 2017)
A catalytic method for functional group interconversion is immensely important in modern sciences. Here, we report an efficient catalytic conversion of nitroalkenes to highly stereoselective 1-trifluoromethylalkenes at room temperature. This unprecedented metal-free photocatalytic strategy is simple and operates under visible-light irradiation using the commercially available CF3 source.

Nickel-catalyzed direct synthesis of dialkoxymethane ethers - Subaramanian, Murugan; Bera, Abhijit; Prasad, Bhagavatula L. V.; Balaraman, Ekambaram (Journal of Chemical Sciences, 2017)
A simple and efficient method for the preparation of dialkoxymethane ethers (oxymethylene ethers) from alcohols and paraformaldehyde in the presence of commercially available nickel(II) salt is described. The reaction proceeds readily under neutral, solvent-free conditions using paraformaldehyde as a C-1 source. The present strategy has a broad substrate scope including aliphatic (both primary and secondary) and aromatic alcohols and provides a benign method for the preparation of symmetrical dialkoxymethanes in good yields (up to 89%).

Nickel-catalyzed N-vinylation of heteroaromatic amines via C-H bond activation - Landge, Vinod G.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2017)
Here, we report a ligand- and reductant-free nickel-catalyzed N-vinylation of heteroaromatic amines using biorenewable p-cymene as a solvent. This unprecedented cross-coupling strategy has high functional group tolerance (halides, alkoxy, cyano, chiral motif, etc.) and proceeded via C-H bond activation.
Keywords: Alkylation; Amination Reactions; Anilines; Aryl Chlorides; halides; Monoarylation; O Bonds; Precatalyst; Pyrimidines; Removeble Directing Group

Organo-photoredox catalyzed oxidative dehydrogenation of N-heterocycles - Sahoo, Manoj K.; Jaiswal, Garima; Rana, Jagannath; Balaraman, Ekambaram (Chemistry-A European Journal, 2017)
We report here for the first time the catalytic oxidative dehydrogenation of N-heterocycles by a visible-light organo-photoredox catalyst with low catalyst loading (0.1-1mol%). The reaction proceeds efficiently under base- and additive-free conditions with ambient air at room temperature. The utility of this benign approach is demonstrated by the synthesis of various pharmaceutically relevant N-heteroarenes such as quinoline, quinoxaline, quinazoline, acridine, and indole.

Predesigned metal-anchored building block for in situ generation of Pd nanoparticles in porous covalent organic framework: application in heterogeneous tandem catalysis - Bhadra, Mohitosh; Sasmal, Himadri Sekhar; Basu, Arghya; Midya, Siba P.; Kandambeth, Sharath; Pachfule, Pradip; Balaraman, Ekambaram; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2017)
The development of nanoparticle-polymer-hybrid-based heterogeneous catalysts with high reactivity and good recyclability is highly desired for their applications in the chemical and pharmaceutical industries: Herein, we have developed a novel synthetic strategy by choosing a predesigned metal-anchored building block for in situ generation of metal (Pd) nanoparticles in the stable, porous, and crystalline covalent organic framework (COF), without using conventional reducing agents. In situ generation of Pd nanoparticles in the COF Skeleton is explicitly confirmed' from PXRD, XPS, TEM images, and N-15 NMR spectral analysis. This hybrid material is found to be an excellent reusable heterogeneous catalyst for the synthesis of biologically and pharmaceutically important 2-substituted benzofurans from 2-bromophencils and terminal alkynes via a tandem process with the turnover number up to 1101. The heterogeneity of the catalytic process is unambiguously verified by a mercury poisoning experiment and leaching test. This hybrid material shows superior catalytic performance compared to commercially available homogeneous as well as heterogeneous Pd catalysts.

Room-temperature direct arylation of anilides under external oxidant-free conditions using CO2-Derived Dimethyl Carbonate (DMC) as a 'green' solvent - Sahoo, Manoj K.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Chemistryselect, 2017)
Here, an efficient catalytic protocol for direct C-H bond arylation of anilides under base- and external oxidant-free conditions is reported. This reaction proceeds readily at room temperature using CO2-derived dimethyl carbonate (DMC) as a green solvent under visible-light dual catalysis. Later, application of our strategy for the gram-scale synthesis of Boscalid has been successfully shown. An unprecedented unsymmetrical bis-arylation of anilides is also demonstrated under mild, redox-neutral conditions.

Simple cobalt(II) chloride catalyzed N-alkylation of amines with alcohols - Midya, Siba P.; Mondal, Akash; Begum, Ayesha; Balaraman, Ekambaram (Synthesis-Stuttgart, 2017)
A facile cobalt-catalyzed N-alkylation of amines with alcohols using inexpensive, commercially available CoCl2 center dot 6H(2)O is reported. Employing this readily available cobalt catalyst, a variety of amines with wide functional group tolerance were selectively alkylated under benign conditions.
Keywords: (Hetero)Aromatic Amines; Alcohols; Amination; amines; Anilines; Aromatic-amines; Cobalt Catalysis; Dehydrogenation Borrowing Hydrogen; Efficient Catalysts; Hydrogen Autotransfer; Iridium; N-alkylation; Pincer-complex; Secondary Alcohols; Selective Alkylation

Unified strategy for silver-, base-, and oxidant-free direct arylation of C-H bonds - Sahoo, Manoj K.; Midya, Siba P.; Landge, Vinod G.; Balaraman, Ekambaram (Green Chemistry, 2017)
Here, we report a dual catalytic approach for room temperature direct arylation of C-H bonds with aryldiazonium salts as a simple aryl group donor, also working as an internal oxidant via C-N-2 bond cleavage. This unified strategy has been achieved by the synergistic combination of visible-light metal-free photoredox and palladium catalysis under silver-, base-and/or additive-free conditions. The broad substrate scope, functional group tolerance, excellent regioselectivity and redox-neutral conditions of this process make it attractive for the effective synthesis of a wide range of important N-heterocyclic commodities such as dibenzo [b,d]azepine, carbazole and phenanthridine.

Cobalt-catalyzed acceptorless dehydrogenative coupling of aminoalcohols with alcohols: direct access to pyrrole, pyridine and pyrazine derivatives - Midya, Siba P.; Landge, Vinod G.; Sahoo, Manoj K.; Rana, Jagannath; Balaraman, Ekambaram (Chemical Communications, 2018)
Here, the first example is reported of a new, molecularly defined SNS-cobalt(II) catalyst for the acceptorless dehydrogenative coupling (ADC) of unprotected amino alcohols with secondary alcohols leading to pyrrole and pyridine derivatives.

Direct access to N-alkylated amines and imines via acceptorless dehydrogenative coupling catalyzed by a cobalt(ii)-NNN pincer complex - Midya, Siba P.; Pitchaimani, Jayaraman; Landge, Vinod G.; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
A simple, phosphine-free Co(ii)-NNN pincer complex catalyzed direct N-alkylation of anilines with alcohols via hydrogen auto-transfer (HA) and selective acceptorless dehydrogenative coupling (ADC) of benzylamines with alcohols affording imines with the liberation of molecular hydrogen and water is reported.

Efficient solar light-driven H-2 production: post-synthetic encapsulation of a Cu2O co-catalyst in a metal-organic framework (MOF) for boosting the effective charge carrier separation - Karthik, Peramaiah; Balaraman, Ekambaram; Neppolian, Bernaurdshaw (Catalysis Science & Technology, 2018)
The development of new and efficient catalytic systems for solar light-driven hydrogen generation is one of the prime focuses of contemporary chemical sciences. Indeed, the charge carrier separation efficiency of a photocatalyst plays a vital role in photocatalysis. Herein, we have successfully designed a Cu2O-encapsulating NH2-MIL-125(Ti) MOF by a post-synthetic encapsulation strategy. The Cu2O-encapsulating MOF material showed a remarkable enhancement in photocatalytic H-2 production activity under solar light illumination. Gratifyingly, the H-2 production activity under solar light was around approximate to 28-fold higher than that of the pristine MOF. The enhancement in photocatalytic activity may be attributed to efficient charge carrier separation through Ti3+ sites and the broad light absorption of the Cu2O-encapsulating MOF photocatalyst. The possible electron transport mechanism, potential energy diagram (V vs. NHE), and the existence of Ti3+ ions have been demonstrated by various spectroscopic studies.

Manganese catalyzed N-alkylation of anilines with alcohols: ligand enabled selectivity - Landge, Vinod G.; Mondal, Akash; Kumar, Vinit; Nandakumar, Avanashiappn; Balaraman, Ekambaram (Organic and biomolecular chemistry, 2018)
Ligand enabled Earth-abundant manganese catalyzed N-alkylation of amines with alcohols via a hydrogen auto-transfer strategy is reported. The choice of the ligand plays a significant role in the alcohol reactivity (aliphatic or aromatic) toward N-alkylation reactions.

Ni-catalyzed alpha-alkylation of unactivated amides and esters with alcohols by hydrogen auto-transfer strategy - Midya, Siba P.; Rana, Jagannath; Pitchaimani, Jayaraman; Nandakumar, Avanashiappan; Madhu, Vedichi; Balaraman, Ekambaram (CHEMSUSCHEM, 2018)
A transition-metal-catalyzed borrowing hydrogen/hydrogen auto-transfer strategy allows the utilization of feedstock alcohols as an alkylating partner, which avoids the formation of stoichiometric salt waste and enables a direct and benign approach for the construction of C-N and C-C bonds. In this study, a nickel-catalyzed alpha-alkylation of unactivated amides and ester (tert-butyl acetate) is carried out by using primary alcohols under mild conditions. This C-C bond-forming reaction is catalyzed by a new, molecularly defined nickel(II) NNN-pincer complex (0.1-1 mol %) and proceeds through hydrogen auto-transfer, thereby releasing water as the sole byproduct. In addition, N-alkylation of cyclic amides under Ni-catalytic conditions is demonstrated.

Ni-catalyzed dehydrogenative coupling of primary and secondary alcohols with methyl-N-heteroaromatics - Rana, Jagannath; Babu, Reshma; Subaramanian, Murugan; Balaraman, Ekambaram (Organic Chemistry Frontiers, 2018)
Here we report the first base-metal catalyzed dehydrogenative coupling of primary (aromatic, heteroaromatic, and aliphatic) and secondary alcohols with methyl-N-heteroaromatics to form various C(sp(3))-alkylated N-heteroaromatics. The reaction is enabled by Earth abundant, non-precious NiBr2 as a transition metal catalyst and N,N,N,N-tetramethylethylenediamine (TMEDA) as a ligand system. Mechanistic studies reveal that a hydrogen auto-transfer process is involved in the direct C(sp(3))-alkylation and the reaction proceeds through an -olefination process.

Pd(II)-Catalyzed gamma-C(sp(3))-H alkynylation of amides: selective functionalization of R chains of amides (RC)-C-1(O)NHR - Landge, Vinod G.; Parveen, Ayisha; Nandakumar, Avanashiappan; Balaraman, Ekambaram (Chemical Communications, 2018)
The gamma C(sp(3))-H bond alkynylation of R chains of amides (RC)-C-1(O)NHR, a fundamental class of synthetic substrates, has not been accomplished to date. Here, the first example of palladium(ii)-catalyzed alkynylation of an unactivated gamma C(sp(3))-H bond of alkyl amides (cyclic, linear, and amino acids) is reported. The kinetic experiment shows that the rate of the reaction depends on the coupling partners and the amides. Late-stage diversification of alkynylated amides was developed by utilizing amine and alkyne functionalities.

Phosphine-free cobalt pincer complex catalyzed Z-selective semi-hydrogenation of unbiased alkynes - Landge, Vinod G.; Pitchaimani, Jayaraman; Midya, Siba P.; Subaramanian, Murugan; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
Herein, we report a novel, molecularly defined NNN-type cobalt pincer complex catalyzed transfer semi-hydrogenation of unbiased alkynes to Z-selective alkenes. This unified process is highly stereo-and chemo-selective and exhibits a broad scope as well as wide functional group tolerance. Ammonia-borane (AB), a bench-stable substrate with high gravimetric hydrogen capacity, was used as a safe and practical transfer hydrogenating source.

Photocatalysis enabling acceptorless dehydrogenation of diaryl hydrazines at room temperature - Sahoo, Manoj K.; Saravanakumar, Krishnasamy; Jaiswal, Garima; Balaraman, Ekambaram (ACS Catalysis, 2018)
Aromatic azo compounds are privileged structural motifs, and they exhibit a myriad of pharmaceutical as well as industrial applications. Here, we report a catalytic acceptorless dehydrogenation of diarylhydrazine derivatives to access a wide variety of aryl-azo compounds with the removal of molecular hydrogen as the sole byproduct. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and Co(dmgH)(2)(py)Cl as the proton-reduction catalyst. The reaction proceeds smoothly under very mild and benign conditions and operates at ambient temperature. This dual catalytic approach is highly compatible with many different functional groups and has a broad substrate scope. We have also demonstrated the reversible hydrogen storage and release phenomenon on hydrazobenzene/azobenzene couple to show the utility of these compounds as hydrogen storage materials. Further diversification of azobenzene was shown by a transition metal-catalyzed azo-group-directed ortho-C-H bond functionalization.
Keywords: acceptorless dehydrogenation; Azo benzene; dual catalysis; Hydrogen; photoredox catalysis

Manganese-catalyzed direct C-C coupling of -C-H bonds of amides and esters with alcohols via hydrogen autotransfer - Rana, Jagannath; Gupta, Virendrakumar; Balaraman, Ekambaram (Dalton Transactions, 2019)
Herein we report an efficient manganese-catalyzed C-alkylation of unactivated amides and tert-butyl acetate using alcohols as alkylating agents. This elegant approach exhibits a broad substrate scope providing the C-C coupled products of amides via a hydrogen auto-transfer strategy using aryl, heteroaryl, and aliphatic alcohols.

Molecular cobalt(II) complexes for tau polymerization in Alzheimer's disease - Gorantla, Nalini Vijay; Landge, Vinod G.; Nagaraju, Pramod Gudigenahally; Priyadarshini, Poornima C. G.; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (ACS Omega, 2019)
Tau is an axonal protein known to form abnormal aggregates and is the biomarker of Alzheimer's disease. Metal-based therapeutics for inhibition of Tau aggregation is limited and rarely reported in contemporary science. Here, we report the first example of rationally designed molecular cobalt(II)-complexes for effective inhibition of Tau and disaggregation of preformed Tau fibrils. The mechanistic studies reveal that prevention of Tau aggregation by cobalt-based metal complexes (CBMCs) is concentration-dependent and Tau seldom exhibits conformational changes. Interestingly, CBMCs play dual role in causing disassembly of preformed aggregates as well as inhibition of complete Tau aggregation. Furthermore, CBMCs were nontoxic and maintained the tubulin network intact. CBMCs also prevented okadaic acid-induced toxicity in SH-SY5Y cells thus, preventing hyperphosphorylation of Tau. We believe that this unprecedented finding by the newly developed molecular complexes has a potential toward metal-based therapeutics for Alzheimer's disease.

Nickel(ii)-catalyzed direct olefination of benzyl alcohols with sulfones with the liberation of H-2 - Landge, Vinod G.; Yadav, Vinita; Subaramanian, Murugan; Dangarh, Pragya; Balaraman, Ekambaram (Chemical Communications, 2019)
A nickel(II)-catalyzed direct olefination of benzyl alcohols with sulfones to access various terminal and internal olefins with the liberation of hydrogen gas is reported.

Reusable cobalt catalyst for reversible acceptorless dehydrogenation and hydrogenation of N-Heterocycles - Jaiswal, Garima; Subaramanian, Murugan; Sahoo, Manoj K.; Balaraman, Ekambaram (ChemCatChem, 2019)
<span style="color: rgb(42, 45, 53); font-family: "Source Sans Pro", Arial, Helvetica, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(248, 248, 248);">The development of robust catalytic systems based on basemetals for reversible acceptorless dehydrogenation (ADH) and hydrogenation of feedstock chemicals is very important in the context of ` hydrogen storage'. Herein, we report a highly efficient reusable cobalt-based heterogeneous catalyst for reversible dehydrogenation and hydrogenation of N-heterocycles. Both the ADH and the hydrogenation processes operate under mild, benign conditions.

Room temperature catalytic dehydrogenation of cyclic amines with the liberation of H-2 using water as a solvent - Sahoo, Manoj K.; Balaraman, Ekambaram (Green Chemistry, 2019)
Catalytic dehydrogenation of cyclic amines, in particular partially saturated N-heterocycles to N-heterocyclic arenes, with the removal of molecular hydrogen as the sole byproduct in water is reported. This dehydrogenation reaction proceeds smoothly under very mild and benign conditions and operates at room temperature. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and a newly synthesized cobalt complex as the proton-reduction catalyst. A detailed mechanistic study (control experiments, electrochemical studies, UV-visible experiments) is presented for the present dual catalysis.

Triazine functionalized porous covalent organic framework for photo-organocatalytic E-Z isomerization of olefins - Bhadra, Mohitosh; Kandambeth, Sharath; Sahoo, Manoj K.; Addicoat, Matthew; Balaraman, Ekambaram; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Visible light-mediated photocatalytic organic transformation has drawn significant attention as an alternative process for replacing thermal reactions. Although precious metal/organic dyes based homogeneous photocatalysts have been developed, their toxic and nonreusable nature makes them inappropriate for large-scale production. Therefore, we have synthesized a triazine and a keto functionalized nonmetal based covalent organic framework (TpTt) for heterogeneous photo catalysis. As the catalyst shows significant absorption of visible light, it has been applied for the photocatalytic uphill conversion of trans-stilbene to cis-stilbene in the presence of blue light-emitting diodes with broad substrate scope via an energy transfer process.

Cobalt-based metal complexes prevent repeat tau aggregation and nontoxic to neuronal cells - Gorantla, V. Nalini; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease (AD) is a fatal neurodegenerative disorder with an alarming increase in the death rate every year. AD is characterised by an aberrant accumulation of proteins in the form of aggregates. The axonal microtubule-associated protein Tau and arnyloid-beta undergo structural transition to beta-sheet rich structure and form aggregates in neuronal soma as well as in the extracellular region. The loss of Tau from microtubules leads to the disintegration of axon and causing neuronal degeneration. This led to the development of effective drugs against AD, to prevent Tau aggregation. Here, we synthesized and screen metal-based complexes to prevent Tau protein aggregation. ThS fluorescence and TEM suggested the role of synthetic cobalt complexes in inhibiting Tau aggregation. CD spectroscopy showed that these complexes prevented conformational changes in Tau to beta-sheet. CBMCs were not toxic at lower concentrations and formed non-toxic Tau species. L1 and L2 prevented membrane leakage: whereas, higher concentrations of L3 caused membrane leakage as observed by LDH release assay. The overall results indicate the synthetic cobalt complexes to be a promising molecule against AD. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cobalt-based metals; Tau Aggregation; Tau inhibition; Tau toxicity

Iron-catalyzed direct julia-type olefination of alcohols - Landge, Vinod G.; Babu, Reshma; Yadav, Vinita; Subaramanian, Murugan; Gupta, Virendrakumar; Balaraman, Ekambaram (Journal of Organic Chemistry, 2020)
Herein, we report an iron-catalyzed, convenient, and expedient strategy for the synthesis of styrene and naphthalene derivatives with the liberation of dihydrogen. The use of a catalyst derived from an earth-abundant metal provides a sustainable strategy to olefins. This method exhibits wide substrate scope (primary and secondary alcohols) functional group tolerance amino, nitro, halo, alkoxy, thiomethoxy, and S- and N-heterocyclic compounds) that can be scaled up. The unprecedented synthesis of 1-methyl naphthalenes proceeds via tandem methenylation/double dehydrogenation. Mechanistic study shows that the cleavage of the C-H bond of alcohol is the rate-determining step.

Manganese-catalyzed alpha-olefination of nitriles with secondary alcohols - Yadav, Vinita; Landge, Vinod G.; Subaramanian, Murugan; Balaraman, Ekambaram (ACS Catalysis, 2020)
An expedient catalytic approach for alpha-olefination of nitriles using secondary alcohols with the liberation of molecular hydrogen and water as the only byproducts is reported. This reaction is catalyzed by a molecularly defined manganese(I) pincer complex and operates in the absence of any hydrogen acceptors. A broad range of substrates including cyclic, acyclic, and benzylic alcohols, as well as various nitrile derivatives, such as arylmethyl and heteroarylmethyl nitriles, are employed in the reaction to provide a diverse range of alpha-vinyl nitriles in good to excellent yields. Mechanistic studies showed that the reaction proceeds via dehydrogenative pathway and the activation of alpha(C-H) bond of the alcohol is the rate-determining step.
Keywords: acceptorless dehydrogenation; Alcohol; alpha-olefination; Hydrogen; manganese

Transition metal nickel prevents Tau aggregation in Alzheimer's disease - Gorantla, Nalini Vijay; Das, Rashmi; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease is the leading cause of dementia, effecting majority of aged people worldwide. The multifaceted effectors of Alzheimer's disease primarily include Tau, amyloid-beta along with hyper activation of kinases, oxidative stress and mutations etc., makes it challenging to design therapeutics. Tau is a microtubule-associating protein, which is subjected to cellular stress resulting in the formation of neurofibrillary tangles, leading to loss of affinity for microtubules. This causes loss of microtubule stability and in turn alters axonal integrity. In the present work, emphasis towards understanding interaction of nickel with Tau was made. Metals such as iron, zinc, copper and lead etc., are known to modulate Tau conformation and enhance its aggregation. Our results showed the deliverance of Tau aggregation by nickel and its synthetic morpholine conjugate. Nickel prevents aggregation by inducing degradation of Tau as evidenced by SDS-PAGE and TEM. Nickel and the synthetic conjugate being non toxic to neuro2a cells and prevent Tau aggregation, might direct these complexes to overcome AD. (C) 2019 Published by Elsevier B.V.
Keywords: Aggregation; Alzheimer's disease; metals; Morpholine; Nickel chloride; Tau

Convenient semihydrogenation of azoarenes to hydrazoarenes using H-2 - Sahoo, Manoj K.; Sivakumar, Ganesan; Jadhav, Sanjay; Shaikh, Samrin; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2021)
The high atom-economical and eco-benign nature of hydrogenation reactions make them much more superior to conventional reduction and transfer hydrogenation. Herein, a convenient and highly selective hydrogenation reaction of azoarenes using molecular hydrogen to access diverse hydrazoarenes is reported. The present catalytic method is general and operationally simple, and it operates under exceedingly mild conditions (room temperature and 1 atm of hydrogen pressure). The reusability of catalysts used in this method is also successfully demonstrated.

Insights into the nature of self-extinguishing external donors for ziegler-natta catalysis: a combined experimental and DFT study - Vipin Raj, K.; Kumawat, Jugal; Dhamaniya, Sunil; Subaramanian, Murugan; Balaraman, Ekambaram; Kumar Gupta, Virendra; Vanka, Kumar; Grubbs, Robert H. (ChemCatChem, 2021)
Developing donors for Ziegler-Natta (ZN) catalysis to control the polymerization reaction and produce polymers with desirable properties has always been challenging due to the multi-component nature of the catalytic systems. Here, we have developed a new synthetic protocol for making two external donors, D-1 (2,2,2-trifluoroethyl myristate) and D-2 (2,2,2-trifluoroethyl palmitate) that show self-extinguishing properties, followed by a systematic DFT study to understand this peculiar property of these donors. D-1 and D-2 can undergo parallel reactions with aluminum and titanium species present in the system to produce ketones and aldehydes, which are poisons for ZN catalytic systems, thus explaining their self-extinguishing nature. The non-covalent interaction between the long alkyl chain of the donors with the surface plays a vital role in determining the donors ` self-extinguishing nature. There is a significant thermodynamic preference for the binding of the donor with the longer alkyl chain at the titanium center. The current work, therefore, provides interesting insights into how self-extinguishing donors function in ZN catalytic systems.
Keywords: DFT; donors; non-covalent interactions; self-extinguishing; Ziegler-Natta catalysis

Phosphine-free manganese(II)-catalyst enables acceptorless dehydrogenative coupling of alcohols with indoles - Yadav, Vinita; Balaraman, Ekambaram; Mhaske, Santosh B. (Advanced Synthesis & Catalysis, 2021)
Herein, an air-stable, molecularly defined NNN-Mn(II) pincer complex catalyzed acceptorless dehydrogenative coupling of alcohols with indoles is reported. A wide variety of symmetrical and unsymmetrical bis(indolyl)methane derivatives as well as some structurally important products such as Vibrindole A, Turbomycin B alkaloid, Antileukemic, and Anticancer agents were synthesized. Mechanistic studies illustrate the importance of the NH moiety in the complex and the crucial role of metal-ligand cooperation during catalysis.
Keywords: acceptorless dehydrogenation; Alcohol; Indole; manganese; phosphine-free

Recent advances in liquid organic hydrogen carriers: an alcohol-based hydrogen economy - Yadav, Vinita; Sivakumar, Ganesan; Gupta, Virendrakumar; Balaraman, Ekambaram (ACS Catalysis, 2021)
Energy storage and the use of abundantly available feedstock without contributing to the carbon footprint are two significant global challenges. In this regard, the development of high-performance, low-cost, sustainable, and environmentally friendly energy storage and production systems is crucial to fulfill the growing energy demands of the current society. The use of hydrogen will diversify energy sources as it significantly reduces greenhouse gas emissions and environmental pollution during energy conversion. Although the hydrogen economy is quite beneficial, hydrogen storage is still very challenging, and the existing methods suffer from a lot of problems and drawbacks. The conventional liquefaction and compression hydrogen storage technologies are associated with several challenges, including low storage density, boil-off losses, relatively high costs, and safety and transportation concerns. In recent years, liquid organic hydrogen carrier (LOHC) systems have attained a lot of importance as a substitute for the traditional storage methods. Hydrogen storage and transport using LOHCs are based on two-step cycles, such as (i) loading/storage of hydrogen by catalytic hydrogenation of H2-lean compounds and (ii) unloading/releasing hydrogen by dehydrogenating the resulting H2-rich liquids. Since alcohols are widely accessible from various industrial processes or even from biomass-derived precursors, the catalytic acceptorless dehydrogenation of alcohols is an attractive approach for future hydrogen storage applications. Hence, the catalytic dehydrogenation-hydrogenation of alcohols can be used for the development of alcohol-based LOHC systems which are economical, safe, and easy to handle. Further, they are similar to crude oils under ambient conditions and thus are suitable for use in the current energy infrastructure. This Review covers several essential aspects of these developing efficient and abundantly available LOHC systems for efficient hydrogen storage and transport applications. Additionally, reversible LOHC systems based on the catalytic dehydrogenation-hydrogenation of alcohols and their corresponding carbonyl compounds have been discussed.

Tandem acceptorless dehydrogenative coupling-decyanation under nickel catalysis - Midya, Siba P.; Subaramanian, Murugan; Babu, Reshma; Yadav, Vinita; Balaraman, Ekambaram (Journal of Organic Chemistry, 2021)
The development of new catalytic processes based on abundantly available starting materials by cheap metals is always a fascinating task and marks an important transition in the chemical industry. Herein, a nickel-catalyzed acceptorless dehydrogenative coupling of alcohols with nitriles followed by decyanation of nitriles to access diversely substituted olefins is reported. This unprecedented C=C bond-forming methodology takes place in a tandem manner with the formation of formamide as a sole byproduct. The significant advantages of this strategy are the low-cost nickel catalyst, good functional group compatibility (ether, thioether, halo, cyano, ester, amino, N/O/S heterocycles; 43 examples), synthetic convenience, and high reaction selectivity and efficiency.

Nickel-catalyzed direct synthesis of N-substituted indoles from amino alcohols and alcohols - Yadav, Vinita; Jagtap, Sayali G.; Balaraman, Ekambaram; Mhaske, Santosh B. (Organic Letters, 2022)
A one-pot cascade approach for the synthesis of N substituted indoles from amino alcohols and alcohols under additive and base-free conditions with the liberation of water as the only stoichiometric byproduct is reported. The commercially available bench-stable Ni(OTf)2 salt in combination with 1,2-bis(dicyclohexylphosphino)ethane (dcype) is very effective for this unprecedented catalytic transformation. A broad range of substrates including aromatic and aliphatic primary alcohols, cyclic and acyclic secondary alcohols, and various substituted 2-aminophenyl ethyl alcohols are employed in the reaction conditions to provide a diverse range of N-alkylated indoles. Mechanistic studies revealed that the reaction proceeds through tandem N-alkylation via hydrogen autotransfer followed by the cyclization of N-alkylated alcohol intermediate.

Dehydrogenative coupling of alcohols with internal alkynes under nickel catalysis: an access to β-deuterated branched ketones - Subaramanian, Murugan; Gouda, Chandrakant; Roy, Triptesh Kumar; Ganesan, Sivakumar; Banerjee, Subhrashis; Vanka, Kumar; Balaraman, Ekambaram (ACS Catalysis, 2024)
In synthetic organic chemistry, unconventional strategies for advanced chemical synthesis pose interesting and challenging problems. Alcohols act as alkylating agents in the C-C and C-N bond-forming reactions via the dehydrogenative borrowing hydrogen strategy in traditional transition metal catalysis; however, as an acylating agent in the C-C bond-forming reactions is challenging and rarely reported. Here, we report the dehydrogenative coupling of benzylic alcohols with internal alkynes under nickel(II) catalysis, wherein alcohol is used as an acylating agent. This reaction system affords a wide range of alpha-branched aryl ketone derivatives with zero waste generation through the umpolung borrowing hydrogen strategy. Moreover, we have demonstrated the chemodivergent applications of the alpha-disubstituted ketones to other valuable building blocks, including large-scale synthesis of beta-deuterated branched ketones. Several spectroscopic studies, intermediate identification, and density functional theory calculations were performed to elucidate the reaction mechanism.
Keywords: Alcohols; alpha-branched aryl ketones; dehydrogenative coupling; internal alkynes; nickel catalysis; pseudoumpolung

Nickel-catalyzed tandem conversion of paraformaldehyde : methanol to hydrogen and formate/chemo- and stereoselective hydrogenation of alkynes under neutral conditions - Subaramanian, Murugan; Padhy, Subarna Sukanya; Gouda, Chandrakanth; Das, Tamal; Vanka, Kumar; Balaraman, Ekambaram (Catalysis Science and Technology, 2024)
The development of new catalytic protocols for clean and COx-free hydrogen generation from fundamental feedstocks is always interesting and challenging. Herein, we disclose nickel-catalyzed dihydrogen generation from a mixture of paraformaldehyde-methanol under base-free and activator-free conditions. The dihydrogen generation from this redox combination under neutral, oxidative coupling conditions has been integrated with the hydrogen transfer reactions such as chemo- and stereoselective hydrogenation of alkynes in a tandem manner. This unprecedented strategy provides diverse highly stereoselective olefins with excellent tolerance of reducible functional groups such as ether, silyl ether, aldehyde, keto, ester, nitrile, halides including bromo and iodo groups, and heteroarenes. Additionally, we demonstrated catalytic stereo-interconversion of alkenes under benign conditions. The affordable gram-scale synthesis of some important pharmaceutical bioactive molecules has further enhanced their synthetic value. A tandem dihydrogen generation from a mixture of paraformaldehyde-methanol under base-free conditions followed by semihydrogenation of alkynes is reported.